(untitled) (MAUSAM, 1961)
According to reports which appeared in the newspapers, the U.S.S.R. exploded two Nuclear (Hydrogen) bombs on 23 and 30 October 1961 in their testing ground above the arctic ice cap east of Novaya Zemlya Island. Both the explosions are said to have been exploded in the atmosphere at a height of about 50 to 60 km. The first explosion, i.e., on 23 October, has been estimated to be of the order of 30 megatons and the second on 30 October, has been estimated to he more than 50 megatons. The explosion on 23 October was recorded by the Seismological Observatory at Upsala (Sweden) at 0811 35m 51s GMT. The French detection services recorded blast wave at 08h 52m GMT from the Novaya Zemlya region in the Arctic. The explosion was also reported to have been recorded by the Royal Netherland Meteorological Service. In Tokyo (Japan) the shock waves started arriving at about 13h 16m GMT. The explosion on 30 October, was detect-ed by various services in Europe and Japan. All the available reports in news-papers sugested that the explosion was 2 to 4 times more powerful than that of 23 October.